Pemberdayaan Mahasiswa Universitas Sains Al-Qur’an dalam Program Kampus Mengajar 5 di SMP Negeri Satu Atap 4 Sukoharjo dan SMPN Satu Atap 3 Kejajar Kabupaten Wonosobo - Robingun Suyud El Syam; Salis Irvan Fuadi; Darul Muntaha (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The Teaching Campus Program is a follow-up program to the Pioneer Teaching Campus Program organized by the Indonesian Ministry of Education and Culture in 2020 as a concrete manifestation of higher education through its students to take part in moving to make education successful nationally in a pandemic situation. The aim of this service is to understand the process of empowering Al-Qur'an Science University students in the Teaching Campus 5 Program at One Roof 4 State Middle School Sukoharjo and One Roof 3 State Middle School Kejajar, Wonosobo Regency. The empowerment strategy goes through four stages, namely: provision, deployment, monitoring and withdrawal. The results of this empowerment show that Al-Qur'an Science University students in the Teaching Campus Program have contributed to solving the problems of post-pandemic education, namely the lack of motivation to learn. This can be seen from the increase in school literacy and numeracy, as well as improved school adaptation to technology in the learning process, and the realization of a project to strengthen the profile of Pancasila students (P5). These results contribute to school recovery after the Covid-19 pandemic. The conclusion focuses on the importance of emotional ties between students and the school in realizing a goal to be achieved together and its implications for the sustainability of national education.